Clinical factors influencing knowledge and self‐care practice among adults with type 2 diabetes mellitus - Richard Adongo Afaya; Victoria Bam; Alberta Yemotsoo Lomotey; Agani Afaya (Nursing Open, 2023)
Abstract Aim The objective of the study was to determine the clinical factors associated with knowledge and self‐care practice among adults living with type 2 diabetes mellitus. Design Descriptive cross‐sectional design. Methods A convenience sample of 330 participants was recruited over 3‐months in 2018 and data were collected using a structured instrument. Results Participants on insulin treatment modality had four times higher odds of knowledge on diabetes (B = 4.17, p = 0.023) while those on combined therapy (both oral hypoglycaemic agent and insulin) had 7.26 times higher odds of knowledge (B = 7.26, p < 0.001). Participants without medically confirmed diabetic complications had 3.66 higher odds of knowledge of diabetes (B = 3.66, p = 0.002). Participants on insulin treatment modality had a 1.4‐fold higher odds of self‐care practice (B = 1.4, p = 0.028). It was revealed that participants with hypertension and diabetic foot had lower odds of self‐care practice (B = −1.13, p = 0.021). Conclusion In particular, participants who were on insulin and combined therapy (tablet and insulin) had higher knowledge and better self‐care practice. Self‐care was significantly influenced among those with, than those without diabetic foot and hypertension as complications.